Validating Scope Design in Project STTF Case Study PT.XYZ - Agustian Mauludin; Wawan Tripiawan; Achmad Fuad Bay (School of Industrial and System Engineering, Telkom University, 2020)
PT.XYZ is a company in the Telecommunication Industry. Due to increase theproduct sales, PT.XYZ performed an annual project to build network infrastructureto the uncovered network areas, called the STTF project. As a project owner,conducting a high performance of scope validation is very crucial to make sure thequality of the result meets requirements. However, the previous project result hasshown to the unsatisfactory result, i.e. titled pole resulting in high cable attenuationand over budget. To see the extent of the performance and effectiveness of thevalidation process, an evaluation of the current validate scope process is necessary.One of the methods is by comparing the operational implementation in the currentSTTF project against the project management standard to ensure the processperformed effectively. Data collected using a questionnaire based on PMBOK 6thed. standard processes using a self-assessment survey, and two project locations arechosen as a comparative sample. The verified questionnaires then distributedpurposively to validate the scope team. In the end, the result of the research showsthe implementation of validate scope activity is not comply with the standard processin PT.XYZ and there are gaps against standard practices in PMBOK.